Pengajaran Al-Qur'an bagi Penyandang Tunanetra: Studi Pengajaran Al-Qur’an Braille di Palembang dan Bengkulu - Jaeni, Ahmad (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
The teaching of the Qur’an is a fundamental requirement of Muslims, including for the visually impaired. The opportunity to acquire the teaching of the Qur'an for the visually impaired is still facing a number of issues starting from the access to the teaching centers, the availability of teachers, the methods and the approaches, the textbooks as well as the support from society and government. In addition to that, the lack of studies relating to this issue has made the problem get less attention. This research was conducted in order to get the portrait of the teaching of the Qur'an for the visually impaired with all the problems and challenges. This paper concludes that the teaching of the Qur'an with Braille script in general still face a number of problems that hinder the effectiveness of its teaching. These issues include the allocation of time, the availability and the competence of the teachers, the standard of the teaching materials, the use of the media and the teaching aids, as well as the lack of support from a number of parties. The Ministry of Religious Affairs which is responsible for Islamic education should take a part actively in preparing the teaching of the Qur’an with Braille script by providing the teaching guidelines. Besides that, the Ministry of Religious Affairs also need to actively prepare the competent teaching staff by conducting the training or education.